Fatal dive : solving the World War II mystery of the USS Grunion - Stevens, Peter F. 1955- (Regnery Publishing, 2012)
Examines one of the enigmas of WWII, the fate of the submarine USS Grunion that vanished without a trace in 1942 carrying a crew of 70 men and the Navy's new top-secret MK 14 torpedoes.